Effect of Mixed Rare Earths on the Wetting Behavior and Interfacial Reaction between Sn-0.70Cu-0.05Ni Solder and Amorphous Fe84.3Si0.3B5.4 Alloy - Hou Bin; Liu Fengmei; Wang Hongqin; Zhang Yupeng; Yi Jianglong; Qin Hongbo (MATEC Web of Conferences, 2018)
In order to explore the effect of addition of mixed rare earths (MRE) on the wetting behavior and interfacial reaction between Sn-0.70Cu-0.05Ni solder and amorphous Fe84.3Si10.3B5.4 alloy, 0.25 wt.% percentage of the MRE, which are mainly elements La and Ce, were added into the solder. Results show it can refine the microstructure of the solder alloy, and there is limited change of melting temperature with the addition of MRE in the solder. The wettability of the solder on amorphous substrate is improved by adding 0.25 wt.% percentage of the MRE into Sn-0.70Cu-0.05Ni solder. Moreover, research results indicate that, with the increase of wetting temperature, the final equilibrium wetting angles of Sn-0.70Cu-0.05Ni and Sn-0.70Cu-0.05Ni-0.25MRE on amorphous substrate decrease gradually, indicating the better wettability at the higher wetting temperature. In addition, with the increase of temperature, the distribution of intermetallic compound (IMC) FeSn2 formed at the interface between the two solders and amorphous substrate is changed from discontinuous state to continuous state. The thickness of the interfacial IMC layer between solder and amorphous substrates reduced with the addition of MRE, indicating that the presence of 0.25 wt.% percentage of the MRE is effective in suppressing the growth of IMC layer.